Efficient multi-component PL emission tunning in single emissive layer (SEL) by amino-functionalized graphene quantum dots in type-II ZnSe/af-GQDs soft core/shell interface as an efficient phosphor. (December 2022) - Mustafa, Faiza; Aslam, Samia; Arshad, Asim; Ahmad, Ashfaq; Sagar, Sadia; Yun, Sining
Highlights: Amino functionalized graphene quantum dots (af-GQDs) employed for the first time as a soft shell to obtain successful synthesis of novel ZnSe/af-GQDs core-shell structures. Passivation of strain induced defects states of ZnSe core via development of af-GQDs soft shell interface. Highly efficient tuning of photoluminescence (PL) emission spectral components in the visible region (∼458nm-750nm). The activation energy Er and escape energy Eesc for radiative and non-radiative recombination respectively estimated using Arrhenius and Berthelot fitting functions. Er and Eesc values indicated pronounced decrease in non-radiative recombination in ZnSe/af-GQDs. Mechanism of formation of type-II band alignment in ZnSe/af-GQDs is clarified via applying tight binding model. Abstract: This research demonstrates first report on successful formation of ZnSe/amino functionalized graphene quantum dots (af-GQDs), type-II core-shell structures. The structures having potential as a single emissive layer (SEL), were synthesized via a facile and eco-friendly hot injection method. We achieved a highly efficient tuning of PL emission spectral components in visible region ranging from (∼458 to 750nm). The functional groups attached with af-GQDs rendered soft shell feature to the structures and the soft core-shell interface significantly passivated the strain-induced defect states and reduced Auger recombination (AR). The PL emission properties of ZnSe/af-GQDs were studied through steady state and temperature dependent photoluminescence (TDPL) spectroscopy within the temperature range (80-300k), using 457nm excitation laser. Three samples including bare ZnSe QDs, bare af-GQDs and ZnSe/af-GQDs core/shell structures were prepared. The steady state PL emission spectra revealed a weak blue and pronounced green, yellow, orange and red emission, whereas the full width half maximum (FWHM) of PL spectra distinctly decreased in ZnSe/af-GQDs. The carrier activation and escape energies of radiative and non-radiative recombination respectively were estimated through Arhenious and Brethelot fitting functions for TDPL measurements. The calculated values clearly indicated a decrease in activation energies and an increase in escape energies in ZnSe/af-GQD X-ray photon spectroscopy (XPS) measurements revealed the presence of Zn 2p and Se (3d) O1s and NIs orbitals of constituent elements including Zn, Se, C, O and N. Tight binding model was applied to estimate the valance and conduction band energies that suggested formation of type-II core-shell band alignment in the structures. The relative PLQY was estimated using comparative method and Rhodamine-B was used as reference and calculated PLQY are 58%, 61% and 83% for ZnSe, af-GQDs and ZnSe/af-GQDs. A mechanism of formation of a soft core-shell interface for ZnSe/af-GQDs is clarified. We suggest that ZnSe-/af-GQDs structures synthesized in this report have a great potential for LEDs and display devices in which multi-color components are of paramount importance, such as white light emission. This report may open a gate way for more and vivid possibilities to apply af-GQDs for optoelectronic devices. Graphical abstract: Image, graphical abstract